Prosthetic management of resorbed ridges through fabrication of hollow denture using three-dimensional glycerin spacer and neutral zone technique - Manu Rathee; Sujata Chahal; Prachi Jain; S Divakar; Sandeep Singh; Sarthak Singh Tomar (Wolters Kluwer Medknow Publications, 2022)
Residual ridge resorption leads to diminished retention, support, and stability of the prosthesis due to decrease in the denture supporting areas, decreased denture space, and increased leverage due to increase inter-ridge distance. The prosthetic rehabilitation of the severely resorbed ridges needs modification for the fabrication of a stable prosthesis. This clinical report describes the prosthetic management of resorbed ridges using modified impression technique, neutral zone technique, external impressions, and fabrication of a hollow denture using three-dimensional glycerin spacer to enhance the retention and stability of the prosthesis.